2010
DOI: 10.1038/aps.2009.204
|View full text |Cite
|
Sign up to set email alerts
|

Transforming growth factor-β1 upregulates the expression of CXC chemokine receptor 4 (CXCR4) in human breast cancer MCF-7 cells

Abstract: Aim: To investigate whether rhTGF-β1 or a recombinant vector encoding a fusion protein comprising an extracellular domain of TGF-β receptor II and an IgG Fc fragment) affects the regulation of CXC chemokine receptor 4 (CXCR4) expression in MCF-7 human breast cancer cells. Methods: MCF-7 breast cancer cells were treated with rhTGF-β1 or transfected with a recombinant vector, pIRES2-EGFP-TβRII-Fc. Expression of CXCR4 in these cells was then analyzed at the mRNA and protein levels by quantitative RT-PCR and flow … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(19 citation statements)
references
References 33 publications
0
19
0
Order By: Relevance
“…Recently, studies have confirmed that there is cross-talk between the TGFb and CXCL12 pathways. Evidence indicates that TGFb induces CXCR4 in tumor cells (34), enhancing the response to CXCL12 to promote invasion and metastasis (35). We also revealed that DPP-4 suppression induces TGFb/Smad signaling, but the TGFb-induced CXCR4 cascade was not relevant for DPP-4-induced EMT and metastasis because the KR-induced CXCL12/CXCR4/mTOR axis and EMT were not suppressed by the TGFb-neutralizing antibody.…”
Section: Discussionmentioning
confidence: 69%
“…Recently, studies have confirmed that there is cross-talk between the TGFb and CXCL12 pathways. Evidence indicates that TGFb induces CXCR4 in tumor cells (34), enhancing the response to CXCL12 to promote invasion and metastasis (35). We also revealed that DPP-4 suppression induces TGFb/Smad signaling, but the TGFb-induced CXCR4 cascade was not relevant for DPP-4-induced EMT and metastasis because the KR-induced CXCL12/CXCR4/mTOR axis and EMT were not suppressed by the TGFb-neutralizing antibody.…”
Section: Discussionmentioning
confidence: 69%
“…In response to TGFβ1, rheumatoid synovial T cells also express high levels of CXCR4 and become responsive to SDF‐1α . In addition, Zhao and colleagues showed that MCF‐7 breast cancer cells significantly increased CXCR4 expression after TGFβ1 treatment. Our group has previously shown that TGFβ and its signaling protein, Smad3, are upregulated at sites of arterial injury .…”
Section: Discussionmentioning
confidence: 99%
“…These results suggest that increased receptor numbers, at least in part, contribute to breast cancer metastasis. It has been reported that upregulation of CXCR4 receptors is induced by several oncogenic events such as hypoxia (40), HER2 overexpression (41), EGFR variant-mediated invasion (42) and TGFβ1 signaling (43), suggesting that CXCR4 mediates many oncogenic signals that lead to breast cancer metastasis. CXCL12, the CXCR4 ligand, attracts tumor cells expressing CXCR4 to organs such as the lymph node and bone marrow that produce CXCL12, thereby mediating metastasis.…”
Section: Discussionmentioning
confidence: 99%